2012
DOI: 10.1007/s00415-012-6558-7
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection contributes to high risk of ischemic stroke: evidence from a meta-analysis

Abstract: Chronic infection of Helicobacter pylori (H. pylori) in ischemic stroke (IS) incidence has been previously studied in several publications; however, conflicting results have been reported. A meta-analysis was used to assess whether chronic infection of H. pylori was associated with risk of IS, and which of the following was more effective for predication of IS risk, antibody IgG of H. pylori (anti-H. pylori IgG), antibody IgG of cytotoxin-associated gene-A (anti-Cag A IgG) or the (13)C-urea breath test. We sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 32 publications
0
33
0
2
Order By: Relevance
“…A number of studies have suggested microbes play some role in inflammation, thereby accelerating atherosclerosis [29]. For example, Wang et al conducted a meta-analysis that showed Helicobacter pylori infection contributes to risk of ischemic stroke,[30] however a more recent analysis refuted this [31]. In their meta-analysis, Chen et al found an increased risk of cerebrovascular disease with the presence of IgG for Chlamydia pneumonia [32].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested microbes play some role in inflammation, thereby accelerating atherosclerosis [29]. For example, Wang et al conducted a meta-analysis that showed Helicobacter pylori infection contributes to risk of ischemic stroke,[30] however a more recent analysis refuted this [31]. In their meta-analysis, Chen et al found an increased risk of cerebrovascular disease with the presence of IgG for Chlamydia pneumonia [32].…”
Section: Discussionmentioning
confidence: 99%
“…The problem whether this Recent data showed an association between CagA-positive HP strains and ischemic heart disease (33,34). In addition, it has been suggested that HP might be playing a pathogenic role in rosacea (35).…”
Section: Statement: Increasing Evidence Supports a Negative Associatimentioning
confidence: 96%
“…13,14,20,21 Sample sizes were small in some of these studies 21,25 and some did not control for potential confounders. For example, Heuschmann et al 13 26 and one that included 10 prospective studies reported null results: pooled OR 0.96 (95% CI: 0.78-1.14). Moreover, findings of these studies were conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Heuschmann et al 13 and Coles et al 22 showed no significant association between H pylori seropositivity and ischemic stroke, while Sawayama et al 14 and Masoud et al 21 showed significant positive associations. Results of two meta-analyses were also conflicting; a meta-analysis of 13 case-control studies (4041 participants) showed a positive association: pooled odds ratio (OR) 1.60 (95% confidence intervals [CI]: 1.21-2.11) 26 and one that included 10 prospective studies reported null results: pooled OR 0.96 (95% CI: 0.78-1.14). 27 These two meta-analyses combined results from studies that used different classification methods for both H pylori infection and stroke.…”
Section: Introductionmentioning
confidence: 99%